Gestión de la Demanda en la Industria de Chile: Aprendiendo del Caso Alemán - Masip Macia, Yunesky; Poque González, Axel Bastián; Ramirez Camargo, Luis; Valdes, Javier; Val´ın, Meyli (Ingeniería, 2019)
Context: Both pioneer countries and those that have recently begun an energy transition towards renewable energy require high levels of flexibility in their electrical systems. This article reviews the Demand Side Management (DSM) application as a tool to provide flexibility, and then, to achieve renewable energy penetration objectives. Method: A systematic mini-review of the literature has been done to review the origin and evolution of the concept of DSM in German and Chilean industry, at the same time, to make a parallel and comparison between them. Results: Both countries have difficulties in taking advantage of the demand management potential in the industry, the lack of promoting policies and the lack of specific regulatory frameworks are some of the causes. Conclusions: It is necessary to speed up attention to the management of demand, it is important that the academy contributes with estimates of potential, it also needs public policies that encourage the use of this tool.